El Excentrico, 1949-07-01 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, CA, 2023)
July 1949 [Julio de 1949] Ano 1, No. 2. There is no cover due to this publication using a traditional newspaper format for this issue. The front page contains an article titled, "La Realidad Versus La Fantasia." (transl: Reality vs. Fantasy) The article serves as a reflection of this publication, as well as a resolution for it. The front page also contains photos of Director Humberto Garcia and Prop Master Bessie C. Smith.